Molecular Mechanisms of Foot-and-Mouth Disease Virus Targeting the Host Antiviral Response - Rodríguez Pulido, Miguel; Sáiz, Margarita (Frontiers in Cellular and Infection Microbiology, 2017)
Foot-and-mouth disease virus (FMDV) is the causative agent of an acute vesicular disease affecting pigs, cattle and other domestic, and wild animals worldwide. The aim of the host interferon (IFN) response is to limit viral replication and spread. Detection of the viral genome and products by specialized cellular sensors initiates a signaling cascade that leads to a rapid antiviral response involving the secretion of type I- and type III-IFNs and other antiviral cytokines with antiproliferative and immunomodulatory functions. During co-evolution with their hosts, viruses have acquired strategies to actively counteract host antiviral responses and the balance between innate response and viral antagonism may determine the outcome of disease and pathogenesis. FMDV proteases Lpro and 3C have been found to antagonize the host IFN response by a repertoire of mechanisms. Moreover, the putative role of other viral proteins in IFN antagonism is being recently unveiled, uncovering sophisticated immune evasion strategies different to those reported to date for other members of the Picornaviridae family. Here, we review the interplay between antiviral responses induced by FMDV infection and viral countermeasures to block them. Research on strategies used by viruses to modulate immunity will provide insights into the function of host pathways involved in defense against pathogens and will also lead to development of new therapeutic strategies to fight virus infections.